Solvent Free Extraction for Moringa Oil - Mohammad Faznil Ikwan Md Isa (School of Bioprocess Engineering, University Malaysia Perlis, 2019)
To develop a new process for extraction of moringa oil through solvent free extraction. To analyse boiling point of moringa oil based on pressure and temperature. To apply the knowledge of moringa oil properties obtained from solvent free extraction method for the best yield.